Aladdin and the king of thieves - Wiesner; David (London Parent and Child, 2007)
In this sequel, Aladdin encounters the King of Thieves, a cunning and powerful villain. The plot revolves around Aladdin's efforts to protect his family and kingdom from the King of Thieves' schemes. With the help of his magical lamp and his friends, Aladdin must use his bravery and cleverness to outwit the villain and restore peace. The story emphasizes themes of courage, loyalty, and the triumph of good over evil, while offering an engaging and accessible narrative for young readers.